Pelatihan Kelengkapan Dan Fungsi Obat-Obatan P3K UKS SDN Codo 02 Desa Codo Kabupaten Malang - Novita Qurrotu A’yun; Afwan Hariri; Iman Kukuh Pribadi (Educational Consultant & Counseling Career (EC3) Mataram, 2024)
Training on the Completeness and Function of First Aid Medicines for UKS administrator students at SDN Codo 02, Codo Village, Wajak District, Malang Regency, was held by the State University of Malang KKN Team with the aim of increasing the understanding and skills of UKS administrators in handling health emergencies in the school environment . This activity aims to introduce the importance of having complete medicines in a first aid kit, as well as teaching how to use medicines and first aid equipment correctly in emergency situations. The methods applied in this training include lectures, demonstrations, direct practice, and group discussions. Lectures are used to provide a basic understanding of the types of medicines that should be in the first aid kit and their functions. Then, a demonstration was carried out to show how to use first aid equipment and medicines. Participants are also given the opportunity to practice first aid for minor injuries through direct practice guided by the KKN team. Group discussions were held to encourage participants to think critically and work together in dealing with emergency situations. Through this training, UKS administrators are expected to be more prepared and confident in dealing with emergency conditions that may occur at school, such as accidents or minor health problems. This activity also aims to increase awareness of the importance of providing complete medication and its correct use, so as to minimize health risks and create a safe and healthy school environment. This training is expected to have a positive impact on UKS administrators and students at SDN Codo 02.